Diabetes mellitus in alcohol-dependent individuals – double pathology - Marek, Jerzy; Kowrach, Marek; Luźniak, Paweł (Przewodnik Lekarza/Guide for GPs, 2009)
In the following study the nomenclature and epidemiology of various forms of alcohol abuse syndrome are characterized. Multiple harmful effects of persistent ethanol consumption are listed, including diabetes mellitus secondary to alcohol-induced chronic pancreatitis. The author presents differences in the pathophysiology and clinical course of diabetes mellitus in alcohol-dependent individuals. Dependence-related medical, social and economic problems are highlighted as factors disturbing crucial components of diabetes management (diet, self-monitoring of glycaemia, pharmacotherapy) and significantly limiting the probability of achieving metabolic control. Typical models of diabetes mellitus and alcohol dependence comorbidity are characterized with reference to the potential role of psychotherapy in proposed management.